Dancefloor-driven literature the rave scene in fiction - Morrison, Simon Alexander 1964- (Bloomsbury Academic, 2020)
"Considers club culture via the prism of the fictions written about the subculture - interrogating why, and how, authors write about electronic music as text"--
Includes bibliographical references and index
Keywords: Music in literature; Electronic dance music in literature; Rave culture in literature; English fiction / 20th century / History and criticism; English fiction / 21st century / History and criticism; Electronic music